Representation reconsidered - Ramsey, William M. 1960- (Cambridge University Press, 2007)
Cognitive representation is the single most important explanatory notion in the sciences of the mind and has served as the cornerstone for the so-called 'cognitive revolution'. This book, originally published in 2007, critically examines the ways in which philosophers and cognitive scientists appeal to representations in their theories, and argues that there is considerable confusion about the nature of representational states. This has led to an excessive over-application of the notion – especially in many of the fresher theories in computational neuroscience. Representation Reconsidered shows how psychological research is actually moving in a non-representational direction, revealing a radical, though largely unnoticed, shift in our basic understanding of how the mind works
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Mental representation; Wissensrepräsentation